Globalization of Culture and Identity: Case Study of Halal Tourism Thailand as a Muslim Friendly Tourist Destination - Wahyu Pratama Nur Anggara (Universitas Airlangga, 2022)
Globalization has consequences for the survival of culture. In this discussion, the authors emphasize the study of hybridization as a perspective in seeing the impact of globalization on culture. This can be shown through a case study of Thailand as 'The Kitchen of The World'. Thailand is one of the leading halal food producers, both regionally and internationally. This description emphasizes the author's stance that globalization has contributed to the cultural hybridization of the global halal trend with the identity of the Thai Buddhist population as a Muslim-friendly tourist destination country through halal tourism. Globalization has an influence on the development of an increasingly heterogeneous culture. The spiritual dimension or halal religious values as a foreign culture can also blend with the social conditions of Thai society. Through this explanation, briefly, it is obtained that first, globalization encourages the influence of cultural hybridization through the share of global migrants or in this case Muslim tourists. Both halal are seen as a lifestyle choice instead of emphasizing spirituality or religion reflecting the cosmopolitan sharia. Finally, the development of global culture is aligned with the global economy or halal as a commodity, and on the other hand, Thailand takes the position of being a Muslim-friendly country due to massive global migration as a result of rapid globalization. Keyword: Thailand, Halal Tourism, Globalization, Hybridization